Evaluation Of Waste Management In The Perspective Of UKL-UPL At The Gunung Tinggi Health Center UPT - Susilawati, Susilawati; Mrp, Mimbi Gusrera; Rinanda, Dewi; Purba, Faiqah Adnin; Suhaima, Maznil; Faiza, Mayla (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Environmental Impact Analysis (EIA) in the context of Puskesmas is an environmental assessment instrument used to identify, analyze, and evaluate the potential environmental impact of Puskesmas development and operational activities. The EIA acts as a strategic planning document, providing a basis for the government and activity managers to make the right decisions The Gunung Tinggi Health Center located on Jalan Glugur Rimbun is one of the health facilities planned to improve health services for the surrounding community The Environmental Impact Analysis at the Gunung Tinggi Health Center on Jalan Glugur Rimbun is important to identify, predict, evaluate, and mitigate environmental impacts that may arise from the development and operational activities of the Health Center. The method used is a descriptive survey with direct observation techniques using a checklist sheet based on indicators from the Ministry of Health with indicators of assessment of liquid waste, waste, solids, B3 waste, and facilities & infrastructure. The results of the study show that B3 waste management has been carried out in collaboration with third parties, but liquid waste management is not optimal due to the unavailability of Wastewater Treatment Plants (WWTP). Most solid waste is disposed of directly to the polling station without adequate sorting. Facilities and infrastructure are generally up to standard, but waste management needs to be improved through training, provision of adequate facilities, and a structured monitoring system.